Lipin-1 Contributes to IL-4 Mediated Macrophage Polarization - Chandran, Sunitha (Front Immunol, 2020)
Macrophage responses contribute to a diverse array of pathologies ranging from infectious disease to sterile inflammation. Polarization of macrophages determines their cellular function within biological processes. Lipin-1 is a phosphatidic acid phosphatase in which its enzymatic activity contributes to macrophage pro-inflammatory responses. Lipin-1 also possesses transcriptional co-regulator activity and whether this activity is required for macrophage polarization is unknown. Using mice that lack only lipin-1 enzymatic activity or both enzymatic and transcriptional coregulator activities from myeloid cells, we investigated the contribution of lipin-1 transcriptional co-regulator function toward macrophage wound healing polarization. Macrophages lacking both lipin-1 activities did not elicit IL-4 mediated gene expression to levels seen in either wild-type or lipin-1 enzymatically deficient macrophages. Furthermore, mice lacking myeloid-associated lipin-1 have impaired full thickness excisional wound healing compared to wild-type mice or mice only lacking lipin-1 enzymatic activity from myeloid cell. Our study provides evidence that lipin-1 transcriptional co-regulatory activity contributes to macrophage polarization and influences wound healing in vivo.